The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3847/2041-8213/ab3663
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Carbon Chemistry in a Planetary Nebula: The Unusual Case of K4-47

Abstract: Millimeter molecular line observations have been conducted toward the young (∼900 yr) bipolar planetary nebula (PN) K4-47, using the 12 m antenna and the Submillimeter Telescope of the Arizona Radio Observatory, and the Institut de Radioastronomie Millimétrique 30 m Telescope. Measurements at 1, 2, and 3 mm of multiple transitions were carried out to ensure the accuracy of all molecular identifications. K4-47 was found to be unusually chemically rich, containing three complex species, CH 3 CN, H 2 CNH, and CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Since its first detection, CH 3 CCH has been extensively studied toward star-forming regions (e.g., Zhang et al 2014;Taniguchi et al 2018;Guzmán et al 2018;Bøgelund et al 2019;Calcutt et al 2019), and has proven to be a reliable tracer of their physical conditions (e.g., Bergin et al 1994). It has also been observed toward extagalactic sources, such as M 82, NGC 253, and NGC 1068 (Mauersberger et al, 1991;Qiu et al, 2020), and even toward a planetary nebula, as recently reported by Schmidt and Ziurys (2019). As a matter of fact, the widespread detection of CH 3 CCH even extends to planetary atmospheres (e.g.,…”
Section: The Spectral Tracer Methyl Acetylenesupporting
confidence: 59%
“…Since its first detection, CH 3 CCH has been extensively studied toward star-forming regions (e.g., Zhang et al 2014;Taniguchi et al 2018;Guzmán et al 2018;Bøgelund et al 2019;Calcutt et al 2019), and has proven to be a reliable tracer of their physical conditions (e.g., Bergin et al 1994). It has also been observed toward extagalactic sources, such as M 82, NGC 253, and NGC 1068 (Mauersberger et al, 1991;Qiu et al, 2020), and even toward a planetary nebula, as recently reported by Schmidt and Ziurys (2019). As a matter of fact, the widespread detection of CH 3 CCH even extends to planetary atmospheres (e.g.,…”
Section: The Spectral Tracer Methyl Acetylenesupporting
confidence: 59%
“…It has been proven to be a reliable tracer of physical conditions, such as temperature and density, and has been extensively studied toward star-forming regions (e.g., Buhl & Snyder 1973;Lovas et al 1976;Hollis et al 1981;Kuiper et al 1984;Taniguchi et al 2018;Guzmán et al 2018;Bøgelund et al 2019;Calcutt et al 2019). It has also been observed toward extragalactic sources, such as M 82, NGC 253, and NGC 1068 (Mauersberger et al 1991;Qiu et al 2020), and toward a planetary nebula (Schmidt & Ziurys 2019).…”
Section: The Molecule: Methyl Acetylenementioning
confidence: 95%
“…It is as low as about 20 to 25 in the Galactic center region [21,26,27,28], increases to about 68 in the Solar neighborhood and even further in the outskirts of the Milky Way [21,29,30]. Much lower 12 C/ 13 C ratios than 20 were found in the envelopes of some late-type stars, for example ∼10 for CRL618 [12,31], ∼4 for CK Vulpécula [32], and ∼2 for K4−47 [14,33].…”
Section: Introductionmentioning
confidence: 95%
“…Temperatures of other starforming regions were determined via early propyne observations, such as Orion and DR 21 [6], and of many other sources, including the cold and dense star-less core TMC-1 [7,8]. The molecule was also detected in near-by galaxies, such as M82 and NGC253 [9], in more distant galaxies, such as the foreground galaxy at z ≈ 0.89 in the direction of the quasar PKS 1810−211 [10], in translucent molecular clouds [11], and in the envelopes of late-type stars, such as the protoplanetary nebular CRL618 [12], the asymptotic giant branch star CW Leonis [13] and the planetary nebula K4−47 [14]. Infrared observations with Voyager led to the detection of CH 3 CCH in the atmosphere of Titan [15]; the ISO satellite was employed later to discover propyne in the atmospheres of Saturn [16], Jupiter [17], and Uranus [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation